Pengaruh Sales Growth, Ukuran Perusahaan, Profitabilitas, Likuiditas dan Leverage terhadap Nilai Perusahaan : (Studi Empiris pada Perusahaan Sub Sektor Properties & Real Estate yang Terdaftar di BEI Periode 2019-2023) - Isti Handayani; Wuri Septi Handayani (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This research was conducted aiming to determine the effect of sales growth, company size, profitability, liquidity, and leverage on firm value. This research was conducted at the Properties & Real Estate sector company on the Indonesia Stock Exchange (IDX) with a research period of 2019 - 2023. The sampling technique in this study used purposive sampling with a sample of 51 companies. Based on the research results, it can be concluded that sales growth, company size and liquidity have no effect on company value, then profitability and leverage have a positive effect on company value.